Sistem Pendukung Keputusan Pemberian Jumlah Pinjaman Kepada Calon Nasabah Bumdes Menggunakan Metode Topsis (Studi Kasus Bumdes Gergas Mandiri Kecamatan Wampu) - Wati, Dwi Krisma (Department of Information Technology, Universitas Timor, Indonesia, 2021)
The development of the savings and loan business is currently growing rapidly as a financial institution in alleviating poverty . BumDes is a business owned by a village or sub-district that is engaged in lending or channeling funds to people who need to develop their business. The BUMDes conducts deliberation meetings in determining loan granting. There is often disagreement between the parties that will borrow. This resulted in unequal distribution of loans to BUMDes members. Although the determination of the granting of the loan amount is fully determined by the BUMDes However, this Decision Support System will display the highest to lowest priorities of the prospective customer , so that it will facilitate and assist the BUMDes in making decisions. TOPSIS uses the principle that the chosen alternative must have the closest distance from the positive ideal solution and the longest distance (farthest) from the negative ideal solution to determine the relative proximity of an alternative to the optimal solution.